Questionable ethics--whistle-blowing or tale-telling?. Issue 6 (December 1997) - Chambers, T
Abstract : Renal biopsy is a potentially hazardous procedure, generally performed for therapeutic reasons. An open renal biopsy was performed when there appeared to be no accepted clinical indication and its results published in a specialty journal, whose editors declined publication of subsequent correspondence, questioning the ethical propriety of such a procedure. The implications for clinical practice, authors, editors and readers are discussed.